DISSOCIATIVE IDENTITY DISORDER - Anvarova Rukhshona; Nurmuradov Islomjon (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. Dissociative identity disorder, formerly called multiple personality disorder, is a type of dissociative disorder characterized by the presence of ≥2 alternating identities (also called alter-personalities, ego states, or identities). The disorder includes an inability to recall everyday life events, important personal information, and/or traumatic or stressful events, all of which the person is usually unable to forget in a normal situation. The cause is almost always severe childhood trauma. Diagnosis is based on the collection of a history, sometimes combined with hypnosis or interviews induced by medication. Treatment consists of long-term psychotherapy, sometimes combined with medication therapy in the presence of concomitant depression and/or anxiety [1]. dissociative